PROMOTING INTEGRITY BEHAVIOUR IN FAMILY FIRMS - Rochimat, Dedy; Irawan, Agustinus Purna; Suhartanto, Eko (International Journal of Application on Economics and Business, 2024)
As the family firms grow, they face the challenges of moral hazard and nepotism. To overcome these challenges, family firms should instill integrity values in their family members and employees so that they behave ethically. Integrity strengthens employee effectiveness, loyalty, and ethical behavior, leading to firm performance. This study investigates the emergence of integrity behavior in employees of a family firm. The aim is to examine the relationship between employees' attitudes, subjective norms, perceived behavioral control (PBC), intention, and behavior toward integrity. The study was conducted in an Indonesian public family firm operating as an interior contractor and furniture manufacturer. This study analyzes 433 cases and found a significant positive relationship among these variables. Interestingly, integrity subjective norm is the strongest factor influencing integrity behavior, fully mediated by integrity intention. Considering that integrity attitude should be the most influential factor forming integrity behavior, this study suggests that family firms design a selection process that can recruit candidates with an integrity attitude.